Development of a small molecule-based twophoton photosensitizer for targeting cancer cells - Lee, Dong Joon; Cao, Yu; Juvekar, Vinayak; Sauraj; Noh, Choong Kyun; Shin, Sung Jae; Liu, Zhihong; Kim, Hwan Myung (Journal of Materials Chemistry B, 2024)
Photodynamic therapy (PDT) employing two-photon (TP) excitation is increasingly recognized to induce cell damage selectively in targeted areas, underscoring the importance of developing TP photosensitizers (TP-PSs). In this study, we developed BSe-B, a novel PS that combines a selenium containing dye with biotin, a cancer-selective ligand, and is optimized for TP excitation. BSe-B demonstrated enhanced cancer selectivity, efficient generation of type-I based reactive oxygen species (ROS), low dark toxicity, and excellent cell-staining capability. Evaluation across diverse cell lines (HeLa, A549, OVCAR-3, WI-38, and L-929) demonstrated that BSe-B differentiated and targeted cancer cells while sparing normal cells. BSe-B displayed excellent in vivo biocompatibility. In cancer models such as three-dimensional spheroids and actual colon cancer tissues, BSe-B selectively induced ROS production and cell death under TP irradiation, demonstrating precise spatial control. These findings highlight the potential of BSe-B for imaging-guided PDT and its capability for micro treatment within tissues. Thus, BSe-B demonstrates robust TP-PDT capabilities, making it a promising dual-purpose tool for cancer diagnosis and treatment.
Keywords: Cancer cells; Cell damage; Cell lines; In-vivo; Photosensitiser; Reactive oxygen species; Selective ligands; Small molecules; Two photon; Two-photon excitations; Animals; Antineoplastic Agents; Cell Line, Tumor; Cell Proliferation; Cell Survival; Drug Screening Assays, Antitumor; Humans; Mice; Molecular Structure; Photochemotherapy; Photons; Photosensitizing Agents; Reactive Oxygen Species; Small Molecule Libraries